NOTARIES, MARITAL AGREEMENTS, AND WIVE’S ECONOMIC RIGHTS IN INDONESIA - Mutiara Firsani, Fathya; Effendy, Edrick Edwardina (Pena Cendekia Insani, 2026)
Marriage in Indonesia creates economic legal consequences, particularly regarding marital property and the protection of wives’ economic rights. Marital agreements serve as preventive legal instruments to regulate property ownership, financial responsibilities, and potential asset disputes. This study aims to analyze the role of notaries in ensuring the legal certainty of marital agreements and their effectiveness in protecting wives’ economic rights. This research uses a normative legal method with statutory and conceptual approaches, focusing on Indonesian marriage law, notarial authority, and Constitutional Court Decision No. 69/PUU-XIII/2015. The results show that notarial involvement strengthens the validity, legal certainty, and evidentiary value of marital agreements. Notaries also help formulate clearer and more balanced contractual clauses. However, the effectiveness of marital agreements is influenced by legal culture, public awareness, and clause quality. This study concludes that marital agreements can protect wives’ economic rights when supported by fair clauses and proper notarial guidance.